Priority Analysis of Lean Manufacturing Practices: A Fuzzy-AHP Approach in Automotive Industry. (April 2019) - Galankashi, Masoud Rahiminezhad; Hisjam, Muhammad; Helmi, Syed Ahmad
Abstract: The major aim of this research is to apply a Fuzzy Analytic Hierarchy Process (FAHP) approach to rank the importance of Lean Manufacturing (LM) practices in the automotive industry. Although lean concept is widely investigated in previous literature, highlighting the most important practices of LM in automotive industry is not considered. To fill the gap of previous literature, this study applies a FAHP to prioritize the LM practices in automotive industry. Mainly, the hierarchy structure of the addressed Multiple-Criteria Decision Making (MCDM) approach is as follows. The first level of decision making hierarchy aims to rank the best LM practices using three decision making criteria of the second level. These decision making criteria include application in industry, measurability and managerial acceptance. The third level of decision includes four major practices of LM namely, manufacturing management leanness, management responsibility leanness, workforce leanness and technology leanness. According to the obtained results, technology leanness is the best LM practice to be adopted by automotive manufacturers.